Biodiversidad estacional del macrozoobentos mesolitoral de fondos blandos en la playa de Salaverry, La Libertad – Perú. - Caceres Lescano, Susan Ivett (2016)
The macrozoobenthos biodiversity from the intertidial of Salaverry Beach was carried out between September 2015 and March 2016. Four transects (A, B, C & D) and three sampling stations were established. And the seasonal biodiversity was determined using Shannon - Wiener (H'), Margalef (d'), Pielou (J'), Simpson (λ) and Bray-Curtis index. The samples were collected fortnightly with a 0,028 m2 Penchaszadeh cylinder. Temperature, salinity and granulometry data were also determined. The species were identified with marine invertebrate taxonomic keys. Classes Polychaeta, Nemertea, Gastropoda, Bivalvia, and Malacostraca (Subphylum Crustacea), were recorded. The macrozoobenthos biodiversity in spring was 2,51 bits/ind, and in summer was 1,91 bits/ind with 22 species richness._x000D_ Key words: Biodiversity, Macrozoobenthos, Intertidial, Richness.